The Role of Technology in the NEP 2020 and Its Potential Impact on Teaching and Learning Outcomes: A Study (International Journal of Food and Nutritional Sciences, 2022)
The new education policy in India has emphasized the role of technology in enhancing teaching and learning outcomes. This paper investigates the potential impact of technology on education under the National Education Policy (NEP) 2020 in India and investigate its potential impact on teaching and learning outcomes. The study uses a qualitative approach and is based on a literature review of existing research on technology in education. The study finds that technology has the potential to improve access to education, promote collaborative learning, and enhance students' engagement and motivation. However, technology integration in education also presents several challenges, such as the digital divide, lack of technical skills, and potential distractions. The study suggests that the success of technology integration in education will depend on how effectively it is implemented, with a focus on teacher training, digital infrastructure, and a pedagogical approach that emphasizes active learning, critical thinking and overall educational quality. By examining existing literature, policy documents, and empirical studies, this research paper aims to provide insights into the specific ways technology can support the implementation of the NEP 2020 and its influence on teaching methodologies, curriculum design, assessment practices, and student learning experiences. The findings of this study will inform educators, policymakers, and stakeholders about the potential benefits and challenges associated with technology integration in the context of the NEP 2020.